TANAH SEBAGAI ASET SOSIAL DALAM PERSPEKTIF HUKUM AGRARIA NASIONAL - Joni, H (Jurnal Cakrawala Hukum, 2016)
The land has a strategic function and status, both socially and economically. National Land Body (BPN) as the governmental body who works in land sector has to capale of form and created some policies regarding to dispute and land conflict. There must be a comperehensive to form development strategy that paradigmcally or philosophically rely on Indonesia citizen interests. In order to do that, there must be a whole structuritation toward land form. Technically, it is to utilize information technology development that already become main need in society service. Based on that, social asset which is land is physically not added, but the needs is always increasing, can be managed based on updated values or principles. Those implementation can also be an avant garde in reaching the nation goals to make land as much for social welfare, justice and sustainability of society, nation, and country of Indonesia.